Exploring Financial Risk Management: A Qualitative Study on Risk Identification, Evaluation, and Mitigation in Banking, Insurance, and Corporate Finance - Rumasukun, Muhammad Ridwan; Noch, Muhammad Yamin (Jurnal Manajemen Bisnis, 2024)
The research aims to analyze existing scholarly works to gain insights into risk identification, evaluation, and mitigation strategies. The methodology involves a comprehensive literature search using academic databases such as PubMed, JSTOR, Scopus, and Google Scholar. Inclusion and exclusion criteria are applied to filter relevant sources, and data collection involves reading and critically appraising each selected source. Thematic analysis is employed to identify key findings, themes, and theoretical frameworks. The synthesized findings reveal the importance of risk identification as a fundamental step in effective risk management, encompassing various risks such as credit, market, liquidity, operational, and systemic risks across different sectors. Risk evaluation techniques, including quantitative methods such as value-at-risk modeling and scenario analysis, are crucial for assessing risk impact and likelihood. Risk mitigation strategies, such as financial derivatives, reinsurance, and corporate governance mechanisms, are essential for minimizing risk exposure and enhancing organizational resilience. Challenges such as cybersecurity threats, regulatory complexities, and climate change risks present significant obstacles to risk management. The study highlights the need for integrated risk management approaches that consider emerging threats and uncertainties, promote regulatory cooperation, and leverage technological innovations.